2020
DOI: 10.5194/wcd-1-225-2020
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity in the tropospheric pathway of ENSO to the North Atlantic

Abstract: Abstract. The El Niño–Southern Oscillation (ENSO) can exert a remote impact on North Atlantic and European (NAE) winter climate. This teleconnection is driven by the superposition and interaction of different influences, which are generally grouped into two main pathways, namely the tropospheric and stratospheric pathways. In this study, we focus on the tropospheric pathway through the North Pacific and across the North American continent. Due to the possible nonstationary behavior and the limited time period … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 99 publications
1
18
0
Order By: Relevance
“…Douville, 2009), even if only the zonally symmetric component is imposed (e.g. Simpson et al, 2011;Hitchcock and Simpson, 2014;Zhang et al, 2018;Jiménez-Esteve and Domeisen, 2020). By comparing the difference between the nudged and control ensembles, the processes that drive this downward coupling can be diagnosed in each model for a variety of events of interest.…”
Section: Assess the Mechanisms Underlying Stratospheric Coupling In Individual Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Douville, 2009), even if only the zonally symmetric component is imposed (e.g. Simpson et al, 2011;Hitchcock and Simpson, 2014;Zhang et al, 2018;Jiménez-Esteve and Domeisen, 2020). By comparing the difference between the nudged and control ensembles, the processes that drive this downward coupling can be diagnosed in each model for a variety of events of interest.…”
Section: Assess the Mechanisms Underlying Stratospheric Coupling In Individual Modelsmentioning
confidence: 99%
“…The protocol presented here is primarily based on a zonally-symmetric nudging technique that has been used successfully to identify stratospheric influences on the tropospheric circulation in both hemispheres (Simpson et al, 2011;Hitchcock and Simpson, 2014;Zhang et al, 2018;Jiménez-Esteve and Domeisen, 2020). In essence, by comparing an ensemble hindcast in which the stratosphere is constrained to the observed evolution, to a second hindcast in which the stratospheric circulation is constrained to climatology, the tropospheric impacts of the stratospheric anomalies can be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reanalysis data, we utilize Isca (Vallis et al, 2018), a simplified atmospheric general circulation model (AGCM), to conduct a series of sensitivity experiments. This model uses the Geophysical Fluid Dynamics Labratory (GFDL) dynamical core, and uses the same model configuration as Jiménez-Esteve and Domeisen (2020). The atmosphere does not have explicit liquid water content but instead the moisture and radiative processes are considered using evaporation from the surface and a fast condensation scheme.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This teleconnection is much weaker than the ENSO teleconnection to the Pacific-North American (PNA) region, but is nevertheless the major source for seasonal predictability in the Euro-Atlantic region (e.g., Domeisen et al 2015;Scaife et al 2017). Several pathways have been proposed for ENSO teleconnections to the North Atlantic region, including the canonical tropospheric pathway including the tropical Northern Hemisphere (TNH) pattern (e.g., Wallace and Gutzler 1981;Jiménez-Esteve and Domeisen 2018; and many others) and a stratospheric one (Ineson and Scaife 2009;Butler et al 2014;Domeisen et al 2019). Recent studies have reported that in models and reanalysis there are significant nonlinearities and asymmetries between the ENSO response in the North Pacific (Frauen et al 2014;Garfinkel et al 2019;Jiménez-Esteve and Domeisen 2019), Arctic stratosphere (Rao and Ren 2016;Trascasa-Castro et al 2019;Weinberger et al 2019), and North Atlantic (Hardiman et al 2019;Jiménez-Esteve and Domeisen 2020;Trascasa-Castro et al 2019;Weinberger et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The upperlevel divergence may act as a Rossby wave source (Sardeshmukh and Hoskins 1988) and induce an extratropical wave train, which propagates northeastward from the source region toward the PNA region, eventually reaching the Atlantic region during boreal winter. Transient eddy feedbacks are also essential to zonally extend the anomalies to the North Atlantic (e.g., Li and Lau 2012a,b;Jiménez-Esteve and Domeisen 2018).…”
Section: Introductionmentioning
confidence: 99%